The anti-allergic potential of tea: a review of its components, mechanisms and risks. Issue 1 (26th November 2020) - Li, Qing-Sheng; Wang, Ying-Qi; Liang, Yue-Rong; Lu, Jian-Liang
Abstract : Tea, as a functional beverage, exerts its anti-allergic effects by reducing IgE and histamine levels, decreasing FcεRI expression, regulating the balance of Th1/Th2/Th17/Treg cells and inhibiting related transcription factors. Abstract : Allergy is an immune-mediated disease with increasing prevalence worldwide. Regular treatment with glucocorticoids and antihistamine drugs for allergy patients is palliative rather than permanent. Daily use of dietary anti-allergic natural products is a superior way to prevent allergy and alleviate the threat. Tea, as a health-promoting beverage, has multiple compounds with immunomodulatory ability. Persuasive evidence has shown the anti-allergic ability of tea against asthma, food allergy, atopic dermatitis and anaphylaxis. Recent advances in potential anti-allergic ability of tea and anti-allergic compounds in tea have been reviewed in this paper. Tea exerts its anti-allergic effect mainly by reducing IgE and histamine levels, decreasing FcεRI expression, regulating the balance of Th1/Th2/Th17/Treg cells and inhibiting related transcription factors. Further research perspectives are also discussed.